Pengintegrasian Asas Andragogi dalam Pengembangan Maharah Qira’ah di LPBA MASA Surabaya : Pendekatan Inovatif Pembelajaran Bahasa Arab - Laili Mas Ulliyah Hasan; Muhammad Rido’i (Program Studi Pendidikan Bahasa Arab, 2024)
This research aims to explore and analyze the integration of Andragogy principles in the development of maharah qiro'ah at LPBA MASA Surabaya. The research method uses a qualitative approach with a focus on innovative approaches to learning Arabic. Research participants consisted of students and lecturers who were involved in developing maharah qiro'ah at LPBA. Data was collected through classroom observations, interviews with instructors, and student questionnaires. Research findings show that integrating the principles of Andragogy in the development of maharah qiro'ah makes a significant contribution in creating relevant and effective learning experiences for students. The use of Andragogy principles allows teachers to pay more attention to the independence, experience and learning needs of adult students in developing the ability to read Arabic texts. Challenges in integrating the principles of Andragogy include a lack of appropriate resources and a paradigm shift in learning approaches. However, the potential and benefits are enormous, including improving the quality of Arabic language learning and student motivation in deepening maharah qiro'ah. Recommendations include training and professional development for faculty, increasing access to resources, and developing curricula that are oriented to the learning needs of adult students. This research provides valuable insights for the development of Arabic language learning practices in similar educational institutions.